Implementation of Organization Development Case Study in Bank Muamalat Indonesia - Sulistianing, Rina; Tjakraatmadja, Jann Hidajat (The Indonesian Journal of Business Administration, 2013)
The current position of Bank Muamalat Indonesia (BMI) is in the transformation phase, namely to accelerate business growth. The acceleration is closely related to competitiveness owned by BMI. The trend of diminishing productivity level of BMI’s employees is a challenge for the bank to process improvement.  Some factors that may affect employee’s productivity are the variables of Organization Development (OD) which can be grouped into business strategy variable, technology & organization structure, human resource and human process variable. Measurement of employee’s productivity which is the best practices in BMI is the partial productivity that is based on total assets per employee.  From the results of the assessment of BMI’s Supervisor, so the root causes are following : BMI has not concerned operation efficiency and the customer’s needs in its business strategy; the development & application  of new working methods design and process of product development banking to improve aspects of techno-structural still have not been optimal; the weak utilization of training for the employees’ competencies development which had been obtained by the bank; and there were only a number of people have done sharing and work in ad hoc team. Referring to the results of analysis above, then we can see that the study proposed four (4) basic programs for the improvement of productivity for BMI, namely : (1) Budgetary Control Program (Marketing Budget Improvement & Procurement Function Improvement); (2) Work Design Improvement Program (Standard Operating Procedure (SOP) of Marketing  and Operation Staff’s  Activities Improvement); (3) Training Program (Service Training, Marketing & Time management Training); and (4) Sharing Program (Knowledge Cafe and Board  & Employees Gathering). Keywords : Islamic Banking, Employee’s Productivity, Organization Development